Maxillary Rehabilitation Using Fixed and Removable Partial Dentures with Attachments: A Clinical Report - Dos Santos Nunes Reis, José Maurício; Da Cruz Perez, Luciano Elias; Alfenas, Bruna Fernandes Moreira; De Oliveira Abi-Rached, Filipe; Arioli Filho, João Neudenir [UNESP] (Wiley, 2013)
Despite requiring dental crown preparation and possible root canal treatment, besides the difficulty of clinical and laboratory repairs, and financial burden, the association between fixed (FPD) and removable partial dentures (RPD) by means of attachments is an important alternative for oral rehabilitation, particularly when the use of dental implants and FPDs is limited or not indicated. Among the advantages of attachment-retained RPDs are the improvements in esthetics and biomechanics, as well as correction of the buccal arrangement of anterior teeth in Kennedy Class III partially edentulous arches. This article describes the treatment sequence and technique for the use of attachments in therapy combining FPD/RPD. © 2013 by the American College of Prosthodontists.
Keywords: Extracoronal precision attachments; Fixed partial denture; Removable partial denture